miR-4478 sensitizes ovarian cancer cells to irradiation by inhibiting Fus and attenuating autophagy - Lingling Wang; Ying Liu; Haixia Li; Cui Zhang; Hongbo Wang; Shaochun Dai; Wen Cheng; Yan Sun; Xiulan Zheng (Elsevier, 2021)
Ovarian cancer (OC) is a type of cancer with high prevalence and shocking mortality in women around the world. Radioresistance is a major reason for OC relapse. Mounting studies have shown the significant function of dysregulated microRNAs (miRNAs) in cancer progression and the cellular response to irradiation. The present study inquired about the function and mechanism of microRNA (miR)-4478 in regulating radiosensitivity of OC cells. Results showed that miR-4478 was downregulated in OC, and a low miR-4478 level indicated a disappointing prognosis for OC patients. Besides, in OC cells exposed to irradiation, the expression of miR-4478 decreased over time. Functionally, the upregulation of miR-4478 retarded OC cell proliferation and sensitized OC cells to irradiation. Mechanistically, miR-4478 targeted and inhibited fused in sarcoma (Fus). Additionally, Fus was upregulated in OC and its expression further elevated in OC cells under irradiation. Furthermore, miR-4478 targeted Fus to inhibit autophagy, therefore sensitizing OC cells to irradiation. Collectively, our study uncovered miR-4478 as a novel radiosensitizer by targeting Fus in OC cells, which may shed a new light on developing targets for treating patients with OC, particularly those with radioresistance.